Meningkatkan Pemahaman Membaca Siswa dengan Menggunakan Teknik Buzz Group - Dahlina, Ulinuha (JEDLISH : Journal Of Education and English Language Teaching, 2021)
There are four main skills in English: those are reading, listening, speaking, and writing skills. Reading is the one of skill that the students must have. Based on the researcher’s experience in teaching English at SMP N 3 Pandeglang at eighth grade, the researcher found the students’ reading comprehension was low. One of the suitable technique in teaching reading to the condition of the teaching learning process at the eighth grade of SMP N 3 Pandeglang using Buzz groups technique. This research was conducted to know the process in teaching reading comprehension through Buzz groups technique at the eighth grade students of SMP N 3 Pandeglang and To know the result of teaching reading comprehension through Buzz groups technique at the eighth grade students of SMP N 3 Pandeglang. Related to the purposes of the study the research design used in this study was action research. The subject of the study was the students of class VIII C of SMP Negeri 3 Pandeglang in the academic year 2018/2019. There were 38 students as the subject. The action research was conducted from August to September 2018. In this research, the researcher taught reading by using buzz groups technique. Buzz groups technique is a technique of group discussion which consists of four to six students that are formed to respond the course-related question in order to get ideas that are generated with the feedback and discussed by whole group within a specific period of time. The procedure of this research consists of generating idea, solving a problem or reaching common viewpoint on the topic, and then followed by whole class discussions in large groups to the topic. The writer conducted two cycles of action. In collecting the data, the writer uses qualitative and quantitative technique. The qualitative data are obtained from observation, questionnaire, document analysis, and photograph. The qualitative data are supported by quantitative data that are mean score of students’ pre-test and post-test on reading. In this action research is as the teacher in teaching learning process. Meanwhile, the observer is the English teacher. The results of this research are teaching reading by using buzz groups technique can effectively improve students’ reading comprehension. From the observation, the writer found that during the action, the students have shown their improvement such as they were able to comprehend the text well, the situation of the teaching and learning process became more enjoyable and interesting, and all of the students were involved in the teaching and learning process. They can share their knowledge and help each other in understanding the lesson material. The students not only learn from the teacher explanation, but they can learn from their friend who also learns the same thing. This technique provides opportunities for the students to understand the lesson material more by asking each other group member without being ashamed and afraid, since the students are usually afraid to ask the difficulties to the teacher. From the reading comprehension test, the students’ pre-test mean score was 66.44, increasing to 72.76 in the first post-test and increasing to 83.28 in the final post-test. Therefore, it can be concluded that teaching reading by using buzz groups technique can improve the students’ reading comprehension.